The Effects of Using Duolingo Towards Student’s Vocabulary Mastery (An Experiment of Junior High School Students at Omega Sains Institute) - Kusumadewi, Hermariyanti (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
Learning a foreign language is not so tedious and troublesome through the internet software to be the easiest platform, lots to avail and reach, such as Duolingo. Duolingo deliberately carry the concept of